Dicite, Pierides classical studies in honour of Stratis Kyriakides - Michalopulos, Andreas N.; Papaïōannu, Sophia; Zissos, Paul Andrew 1960- (Cambridge Scholars Publishing, 2017)
Presents essays written in honour of Stratis Kyriakidis, Emeritus Professor of Latin Literature at the Aristotle University of Thessaloniki. Greece. It offers a rich assortment of scholarship on classical literature, ranging from Homeric epic, and the tradition of ecphrasis it spawned in a number of genres, to 17th-century English translations of Virgil's Aeneid. The collection is divided into two sections, the first on Greek literature, and the second on Latin literature